MEANINGFUL LEARNING WITH SETS APPROACH IN BIOLOGY LESSON FOR GROWING CONCERN ON THE ENVIRONMENT - Setyo, Ajib (BIOMA, 2011)
This study aims to develop meaningful learning with SETS approach in photosyn-thetic material to enchance the activity of learning and growing concern for the envi-ronment as well as find out the validity, reliability and effectiveness of the device developed. Research carried out is the research and development. Research subjects were 48 students of SMAN 2 Mranggen, and 84 students of SMAN 1 Demak, each chosen cluster randomly from the entire class of parallel groups that exist. The results of the development of devices have been validated by experts and with the validation of construct values 3.4; syllabus 3.57; of teaching materials and stu-dent worksheets are 3.125; RPP 3.0; and evaluation of learning of 3.125 with either category. Achievement learning activities in the experimental class discussion jig saw 8 percent, 93 percent independent practicum and presentation assessment pho-tosynthetic material SETS 77 percent. Learning is done to foster concern for the envi-ronment by 61.90 percent (very high) and 38.10 percent (high) of 42 students. Me-aningful learning can achieve a classical completeness by 100 percent and improve student learning outcomes for the N-gain of 0.72. Criterion scores showed signifi- cant learning device usage 81 percent, and 90 percent of student responses, the res-ponses of teachers expressed a very meaningful learning tools to create meaningful learning as well. The conclusion of this study is, the learning material with SETS approach on photo-synthesis developed, categorized as very meaningful to enhance the activity of lear-ning and growing concern for the environment.Keywords: learning meaningful, SETS, photosynthesis, activity, environment